muSEAum – Branding the Sea Museums of Portugal Research findings and perspectives of an innovation journey (Revista Lusófona de Educação, 2023)
The presence of the sea in Portuguese museums, monuments and sites is formidable, a multifaceted heritage providing experiences transposing history, exploration, industry, commerce, lifestyles, technologies, architecture, popular and fine arts. muSEAum focused on management competencies for the competitive exploration of museums’ characteristics, environment, and collection. The co-innovation project with a nationwide sample of sea-themed museological institutions – not just maritime or marine museums -- addressed the definition, management and communication of the museum brand, the benefits of a Sea Museum of Portugal collective brand, visitor experience technologies, national and international reach and awareness, spirit of belonging, new learning partnerships, and local tourism. Research on audiences and management practices provided a solid evaluation basis. Notwithstanding some noteworthy, good practices, most institutions suffer from insufficient funding and administrative autonomy. Promotional efforts are geared towards local constituencies leading to residual national and international visibility, affecting particularly those off tourist circuits. Incipient or inexistant brands, inefficient or non-existent websites, inconspicuous SEO and digital marketing activities, own domain names a rarity keep many museums absconded in the internet maelstrom.Key words: maritime heritage; museum; Portugal; branding; museaum